2003
DOI: 10.1074/jbc.m210843200
|View full text |Cite
|
Sign up to set email alerts
|

STAM and Hrs Are Subunits of a Multivalent Ubiquitin-binding Complex on Early Endosomes

Abstract: STAM1 and STAM2, which have been identified as regulators of receptor signaling and trafficking, interact directly with Hrs, which mediates the endocytic sorting of ubiquitinated membrane proteins. The STAM proteins interact with the same coiled-coil domain that is involved in the targeting of Hrs to endosomes. In this work, we show that STAM1 and STAM2, as well as an endocytic regulator protein, Eps15, can be co-immunoprecipitated with Hrs both from membrane and cytosolic fractions and that recombinant Hrs, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
277
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(296 citation statements)
references
References 65 publications
16
277
0
3
Order By: Relevance
“…In contrast, we find that Hrs is not involved in the process. However, the functions of Hrs in lumenal vesicle formation (Lloyd et al, 2002;Bache et al, 2003b;Razi and Futter, 2006) are not clear and may well be indirect (Pons et al, 2008). Although Alix negatively regulates the formation of lumenal vesicles and EGF receptor sorting, our data show that Tsg101 is a necessary component of the budding reaction.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, we find that Hrs is not involved in the process. However, the functions of Hrs in lumenal vesicle formation (Lloyd et al, 2002;Bache et al, 2003b;Razi and Futter, 2006) are not clear and may well be indirect (Pons et al, 2008). Although Alix negatively regulates the formation of lumenal vesicles and EGF receptor sorting, our data show that Tsg101 is a necessary component of the budding reaction.…”
Section: Discussionmentioning
confidence: 70%
“…Evidence shows that this PtdIns3P-, Hrs-, and ESCRT-based sorting mechanism is coupled to the membrane invagination process. The number of intralumenal vesicles within endosomes is decreased after PtdIns 3-kinase inhibition (Reaves et al, 1996;Fernandez-Borja et al, 1999;Futter et al, 2001), and after Hrs knockout in Drosophila melanogaster (Lloyd et al, 2002) or knockdown in mammalian cells (Bache et al, 2003b;Razi and Futter, 2006). Presumably, Hrs, by initiating ES-CRT recruitment, is indirectly responsible for intralumenal vesicle formation (Bache et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that Hrs recruits STAM to the endosomal membrane, and that Hrs, STAM and Eps15 co-localize with ubiquitinated proteins in clathrin-positive microdomains on early endosomes (Asao et al, 1997;Bache et al, 2003). As both Hrs, STAM and Eps15 bind ubiquitinated proteins, they have been suggested to function together in the capture of ubiquitinated proteins for sorting into MVBs (Bache et al, 2003).…”
Section: Endosomal Sorting Of Ubiquitinated Cargomentioning
confidence: 99%
“…Depletion of Hrs or STAM using RNA interference (RNAi) or gene disruption inhibits RTK down-regulation in mammalian cells (Bache et al, 2003b;Hammond et al, 2003;Kanazawa et al, 2003;Lu et al, 2003) and in Drosophila (Lloyd et al, 2002). The budding yeast Saccharomyces cerevisiae also has orthologues of Hrs and STAM, which are Vps27 (vacuolar protein sorting 27) and Hse1 (Hbp/STAM/EAST 1), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Endosomal sorting of ubiquitinated RTKs is initiated by a complex of two Ub-binding proteins, hepatocyte growth factor-regulated substrate (Hrs) and signal-transducing adaptor molecule (STAM), which localizes on the cytoplasmic face of the early endosomal membrane (Komada et al, 1997;Bache et al, 2003b;Mizuno et al, 2003Mizuno et al, , 2004. Depletion of Hrs or STAM using RNA interference (RNAi) or gene disruption inhibits RTK down-regulation in mammalian cells (Bache et al, 2003b;Hammond et al, 2003;Kanazawa et al, 2003;Lu et al, 2003) and in Drosophila (Lloyd et al, 2002).…”
Section: Introductionmentioning
confidence: 99%